1995
DOI: 10.1159/000119209
|View full text |Cite
|
Sign up to set email alerts
|

Amnesia after Diazepam Infusion into Basolateral But Not Central Amygdala of Rattus norvegicus

Abstract: Recent findings indicate that the memory-impairing effects of benzodiazepines may preferentially involve the basolateral nucleus of the amygdala. To test this hypothesis we examined the effects on pretrial injection of diazepam into the central as compared to the lateral/basolateral amygdaloid nuclei on memory for a conditioned avoidance response. Rats were implanted bilaterally with cannulae directed to either the central or lateral/basolateral amygdaloid nuclei. Five to 7 days later they were trained on a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 36 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Therefore, this facilitation of avoidance conditioning could be interpreted as an improvement of memory, although the possibility of an enhancement of anxiety levels in learned fear situations cannot be ruled out. Several reports have suggested that intra-amygdala BRL 46470A [4] as well as peripheral administration of 5-HT3 receptor antagonists ondansetron [1] and granisetron [24] tend to improve memory, while the injection of BZDs had amnesic effects, particularly when injected into the basolateral amygdala [25], Thus, our results are in close agreement with these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this facilitation of avoidance conditioning could be interpreted as an improvement of memory, although the possibility of an enhancement of anxiety levels in learned fear situations cannot be ruled out. Several reports have suggested that intra-amygdala BRL 46470A [4] as well as peripheral administration of 5-HT3 receptor antagonists ondansetron [1] and granisetron [24] tend to improve memory, while the injection of BZDs had amnesic effects, particularly when injected into the basolateral amygdala [25], Thus, our results are in close agreement with these studies.…”
Section: Discussionsupporting
confidence: 92%
“…As we found with glucocorticoids, the basolateral nucleus appears to be the critical region of the amygdala for BZD influences on memory. Infusions of midazolam into the basolateral nucleus impair memory, whereas infusions administered into the central nucleus are ineffective (75).…”
Section: Interactions With Other Neuromodulatory Systemsmentioning
confidence: 99%
“…The first series of experiments demonstrating a selective involvement of the BLA in memory storage showed that lesions of the BLA, but not of the central nucleus of the amygdala, block the memory impairment induced by systemic injection of benzodiazepines [112]. Furthermore, benzodiazepines infused into the BLA impair retention [113], whereas infusion of a benzodiazepine antagonist into the BLA enhances memory [114]. The findings of subsequent experiments suggested a selective involvement of the BLA in mediating noradrenergic influences on memory for many kinds of tasks [115,116].…”
Section: Different Adrenoceptors In the Basolateral Amygdala Are Invomentioning
confidence: 99%